A New Successive Linearization Approach for Solving Nonlinear Programming Problems - Albayrak, Inci; Sivri, Mustafa; Temelcan, Gizem (PRAIRIE VIEW A & M UNIV, DEPT MATHEMATICS, 2019)
In this paper, we focused on general nonlinear programming (NLP) problems having m nonlinear (or linear) algebraic inequality (or equality or mixed) constraints with a nonlinear (or linear) algebraic objective function in n variables. We proposed a new two-phase-successive linearization approach for solving NLP problems. Aim of this proposed approach is to find a solution of the NLP problem, based on optimal solution of linear programming (LP) problems, satisfying the nonlinear constraints oversensitively. This approach leads to novel methods. Numerical examples are given to illustrate the approach.
Keywords: Nonlinear programming problems; Taylor series; Linear programming problems; Hessian matrix; Maclaurin series; Linearization approach; Mathematics